Дослідження печери Антонія в Любечі у 2009 р. - Руденок, В.Я.; Новик, Т.Г. (Археологічні дослідження в Україні, 2010)
In 2009 archaeological season, a cave of St. Anthoniy in Lyubech which existed in the 19th c. and at the beginning of the 20th c. was discovered and partly studied, particularly, the entrance to the underground chapel and the brick supporting wall which shaped it.